Microvascular Surgery Training in National Institute of Burn and Plastic Surgery (NIBPS), DMCH (Journal of Surgical Sciences, 2019)
Microvascular surgery is a standard procedure in various surgical specialities. For the beginner the logical approach is to start the training with the materials like latex gloves and silastic tube, moving to animal cadaver and finally living animal. In all respect, the training in this particular speciality is costly and facilities are very limited in Bangladesh. Microsurgical training laboratory in National Institute of Burn and Plastic Surgery in Dhaka medical College Hospital conducting courses on Basic and Advanced microsurgery training since July’ 2013. In this paper we introduce the importance and low cost opportunity of training, so that skill would be mastered first in the lab and then applied in real life.Journal of Surgical Sciences (2015) Vol. 19 (2) : 52-54